UJI AKTIVITAS ANTIBAKTERI EKSTRAK N-HEKSAN, ETIL ASETAT, DAN ETANOL DAUN DURIAN (Durio zibethinus Linn.) TERHADAP BAKTERI Propionibacterium acnes dan Staphylococcus epidermidis - Shindi Amanda Rizki; Madyawati Latief; Fitrianingsih Fitrianingsih; Havizur Rahman (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
The durian plant is believed to have medicinal properties and has a distinctive name in each region, such as durian selat from Selat Village in Jambi. Parts of the durian plant such as durian skin and durian seeds have been shown to have antibacterial activity. This study aimed to determine the antibacterial activity and the diameter of the inhibition zone of strait durian leaves (Durio zibethinus Linn.) against Propionibacterium acnes and Staphylococcus epidermidis bacteria. Antibacterial activity testing was carried out using the disc diffusion method. Based on the results obtained, n-hexane, ethyl acetate, and ethanol extract of durian leaves have antibacterial activity at 1% to 6% concentration with weak level against Propionibacterium acnes bacteria and moderate level against Staphylococcus epidermidis bacteria. The highest inhibition zone diameter was obtained from ethyl acetate extract 4.76 mm (weak category) against P. acnes bacteria and the highest inhibition zone diameter was obtained from ethyl acetate extract 6.26 mm (medium category) against S. epidermidis bacteria with MIC values ​​(Minimum Inhibitory Concentration) at 1% concentration.